AN ASSESSMENT OF DIVIDENDS OF DEMOCRACY IN BURUKU LOCAL GOVERNMENT AREA OF BENUE STATE NIGERIA (1999 – 2011) - Okeshola, Folashade B.; Igba, Aaron (European Scientific Journal, ESJ, 2013)
Democracy in Nigeria has brought very few gains and these gains have been rendered insignificant by the negative, uncompromising, depressing and devastating state of the nation. Findings show that the dividends of democracy provided by the government for the masses are enjoyed at a low extent. They are also not equitably distributed. The major reason for the non – equitable distribution of dividends of democracy is corruption in governance aside god fatherism, costliness of Nigeria’s democracy, electoral malpractices, ethnicity, religion and externally triggered democracy. It is therefore recommended that corruption, which is the core impediment to our growth and development, has to be tackled aggressively under a willed and purposeful leadership.